Transwomen in The Transition of Body Change: “Will We Be Accepted as Women?” - Vania Pramudita Hanjani; Carolina Retmawati Putri (Endogami: Jurnal Ilmiah Kajian Antropologi, 2024)
Indonesian society is faced with a gender construction that always directs that men should be masculine while women are required to be feminine. But in reality, we are faced with a condition. where there are men who are feminine, which ultimately makes them get stigmatized and discriminated against by society. This condition causes some men to decide to become women (transwomen). This article explores the journey of transwomen in embracing their gender identity through their physical changes. We conducted participant observation along with semi-formal in-depth interviews with 5 transwomen in in the KTS organization (Kebersamaan Transpuan Semarang), to obtain data through the experiences of these transwomen. Through the results of the analysis, we see that the informants experienced emotional and social challenges faced during the transition process, as well as the hope to be accepted as a woman. Until now, they are still trying to be accepted by society despite the long process they have to go through.